MASALAH KESENJANGAN (GAP) PENDIDIKAN SEKOLAH DASAR ANTARA SEKOLAH DIPERKOTAAN DAN DAERAH-DAERAH 3T - Rizki Ananda; Adella Sulistiya; Audia Zulhafmi; Nyssa Alysia Hamda; Rahman Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The educational gap between elementary schools in urban areas and those in 3T regions (Underdeveloped, Frontier, and Outermost) remains a serious issue in Indonesia. Children living in 3T areas often do not receive adequate educational services compared to those in major cities. This disparity is evident in terms of school facilities, the number and quality of teachers, access to technology, and the teaching methods employed. While urban schools are beginning to implement digital learning and have adequate infrastructure, many schools in 3T regions struggle to provide basic educational needs. This imbalance directly impacts students' learning quality and their opportunities for future development. Therefore, efforts to enhance access to and the quality of education in 3T areas are essential to ensure that all children in Indonesia receive equitable and quality education.